User Friendly Dental Clinic Website Design and Development: Improving Dental Health Services and Patient Satisfaction - Setya Wardhana, Erdianto (Edelweiss Applied Science and Technology, 2024)
Promotion in dental health services in Indonesia must adhere to the dental ethics code. One form of promotion is introducing the various services and facilities of a dental clinic. A website can serve as a medium for introducing a dental clinic. This study aims to design and develop a dental clinic website to improve dental health services and patient satisfaction. The research method used is research and development with an action research approach. The study employed the waterfall System Development Life Cycle (SDLC) method. The website development process was based on a needs analysis, which included interviews with the dental clinic owner, website creation, testing, and evaluation using the System Usability Scale (SUS) questionnaire containing 10 Likert-scale questions. The study results showed that the average evaluation score using the SUS questionnaire was 84.3. Consequently, the adjective ratings fell into the "Excellent" category, the acceptability ranges fell into the "Acceptable" category, and the letter grade fell into category A. The conclusion drawn was that developing a dental clinic website prototype provided beneficial results for both the clinic owner and patients, particularly in obtaining information about dental health services.